2020
DOI: 10.1039/d0bm00188k
|View full text |Cite
|
Sign up to set email alerts
|

A Fe3+-crosslinked pyrogallol-tethered gelatin adhesive hydrogel with antibacterial activity for wound healing

Abstract: A tunicate-inspired gelatin-based hydrogel prepared by a simple mixing method, exhibits strong adhesion and antibacterial capacity, and facilitates wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…In particular, in the case of the three SG/CMC IPN gels, cell viability was similar to that of CMC gels, which is known to be non-toxic. It has been reported that hydrogels that form IPN through Fe 3+ coordination do not have cytotoxcity [ 55 , 56 , 57 , 58 , 59 ]. On the other hand, the positive control treated with DMSO showed a cell viability of 25%.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, in the case of the three SG/CMC IPN gels, cell viability was similar to that of CMC gels, which is known to be non-toxic. It has been reported that hydrogels that form IPN through Fe 3+ coordination do not have cytotoxcity [ 55 , 56 , 57 , 58 , 59 ]. On the other hand, the positive control treated with DMSO showed a cell viability of 25%.…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin also has excellent hydrophilicity, which can absorb wound exudate and maintain a moist environment in the wound area. [ 43 ] At the same time, gelatin, as a partial hydrolysate of collagen, can also participate in the deposition of collagen in the wound area, so it is widely used to prepare hydrogel wound adhesives and clinically used to treat skin, [ 44 ] blood vessels, [ 45 ] gastrointestinal tract, [ 46 ] and lung wounds. [ 47 ] Due to the rich of amino groups, gelatin mainly reacts with aldehyde crosslinking agents (such as glutaraldehyde, and amino polysaccharides, etc.)…”
Section: Typical Types Of Hydrogel Adhesivesmentioning
confidence: 99%
“…Indeed, the wet-contact adhesive strengths of the PVA/PTPM NH coatings on both silicate glass and PMMA were much higher than many commercial glues and high-performance polymeric adhesives in literatures (Figure 2h). [39,44,[49][50][51][52][53][54][55][56][57] Even for two surfaces of dissimilar materials, this PVA/PTPM NH could still glue them. For examples, the wet-contact adhesive strengths between glass slides to steel, aluminum and PMMA slides were found to be ≈1091 ± 159, ≈1082 ± 128, and ≈839 ± 83 KPa, respectively (Figure S18, Supporting Information).…”
Section: Structural and Mechanical Characteristics Of Pva/ptpm Hn Ant...mentioning
confidence: 99%